Computer Safety, Reliability, and Security - Hutchison, David ; Kanade, Takeo ; Kittler, Josef ; Kleinberg, Jon M. ; Friedemann Mattern, John C. Mitchell, Moni Naor, Oscar Nierstrasz, C. Pandu Rangan, Bernhard Steffen, Madhu Sudan, Demetri Terzopoulos, Doug Tygar, Moshe Y. Vardi, Gerhard Weikum, Michael D. Harrison, Mark-Alexander Sujan. (Springer, 2017)
467p.